Intrinsic excitonic emission and valley Zeeman splitting in epitaxial MS2 (M = Mo and W) monolayers on hexagonal boron nitride - Cong, Chunxiao (2020)
Two-dimensional (2D) semiconductors, represented by 2D transition metal dichalcogenides (TMDs), exhibit rich valley physics due to strong spin-orbit/spin-valley coupling. The most common way to probe such 2D systems is to utilize optical methods, which can monitor light emissions from various excitonic states and further help in understanding the physics behind such phenomena. Therefore, 2D TMDs with good optical quality are in great demand. Here, we report a method to directly grow epitaxial WS2 and MoS2 monolayers on hexagonal boron nitride (hBN) flakes with a high yield and high optical quality; these monolayers show better intrinsic light emission features than exfoliated monolayers from natural crystals. For the first time, the valley Zeeman splitting of WS2 and MoS2 monolayers on hBN has been visualized and systematically investigated. This study paves a new way to produce high optical quality WS2 and MoS2 monolayers and to exploit their intrinsic properties in a multitude of applications.